Direct Si-Si bonding through self-assembled monolayers - Eow, Desmond Fu Shen (2016)
Currently, the most widely used bonding method is hydrophilic bonding of oxidized surfaces, which provides high bonding strength. The presence of oxide interface leads to high resistivity and limits the practical applications of bonded wafers. Therefore, oxides-free bonding is desired. It can be realized by surface plasma bonding with fast ion beams in a vacuum chamber. However, this bonding method can result in formation of amorphous layer at the bonding interface. Direct wafer bonding through Self-assembled monolayers (SAM) is anticipated to be an enabling method for oxides-free bonding. Organic monolayers can form spontaneously on surface of substrate by adsorption and passivated the surface from oxidation. After high temperature desorption annealing, the two mating surfaces can bond by covalent bonds. [Peer Assessment Review]